Globalization, growth, and poverty (World Bank WashingtonUS, 2002)
Assesses the impact of globalization and examines anxieties about rising inequality, shifting power, and cultural uniformity that it has generated. Proposes an agenda for action, both to enhance the potential of globalization to provide opportunities for poor people and to reduce and mitigate the risks it generates.
Keywords: GLOBALIZATION